Civic Revolutionaries : - Henton, Douglas (Jossey-Bass, 2004)
Civic Revolutionaries offers a practical guide for renewing the great American tradition of spirited, breakthrough community leadership. By their very nature, revolutionary leaders help their communities reconcile the competing values on which our nation was built: individualism and community, freedom and responsibility, trust and accountability, economy and society. Like the Founders, today's civic revolutionaries are extraordinary leaders who are deeply committed to place, not just to specific issues or constituencies. They provide the vital spark, inspiring others who must ultimately own the revolution if it is to be successful. Written for leaders in business, government, education, and community, Civic Revolutionaries features practical guidance and in-depth case studies from communities across the country. The book provides tested advice to both new and seasoned leaders and draws essential lessons from the American revolutionary tradition to demonstrate how to become an effective leader within the community.